2019
DOI: 10.15621/ijphy/2019/v6i5/186839
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kinesio Taping and Manual Therapy With Supervised Exercise Therapy for the Treatment of Shoulder Impingement Syndrome

Abstract: Background: Shoulder Impingement Syndrome (SIS) is a major contributing factor for shoulder pain. Although many therapists use Kinesio Taping (KT) and Manual Therapy (MT) for SIS, no such studies in combination with Supervised Exercise Therapy (SET) have been conducted in the context of Saudi Arabia. Thus, the purpose of this study is to compare the effectiveness of KT and MT with SET in patients with SIS. Methods: Randomized controlled trial. Thirty-two subjects were assigned into two groups (KT with SET and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Six studies investigated the effectiveness of kinesio taping versus passive treatments, including nonsteroidal anti-inflammatory drugs, 26 extracorporeal shock wave therapy, 27 electrotherapy modalities (TENS, hot pack, US), 38 injection, 28,35 and manual therapy. 39 It was observed that there are no significant mean differences on pain intensity by 0.29 cm (95% CI = –0.19, 0.77, P = 0.24) with moderate heterogeneity (I 2 = 73%). When exploring the effects on range of motion, only four studies 28,35,38,39 were allowed us to conduct quantitative analysis.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Six studies investigated the effectiveness of kinesio taping versus passive treatments, including nonsteroidal anti-inflammatory drugs, 26 extracorporeal shock wave therapy, 27 electrotherapy modalities (TENS, hot pack, US), 38 injection, 28,35 and manual therapy. 39 It was observed that there are no significant mean differences on pain intensity by 0.29 cm (95% CI = –0.19, 0.77, P = 0.24) with moderate heterogeneity (I 2 = 73%). When exploring the effects on range of motion, only four studies 28,35,38,39 were allowed us to conduct quantitative analysis.…”
Section: Resultsmentioning
confidence: 92%
“…39 It was observed that there are no significant mean differences on pain intensity by 0.29 cm (95% CI = –0.19, 0.77, P = 0.24) with moderate heterogeneity (I 2 = 73%). When exploring the effects on range of motion, only four studies 28,35,38,39 were allowed us to conduct quantitative analysis. Two studies 28,35 compared kinesio taping with injection and a nonsignificant standard mean difference by 0.06 (95% CI = –0.09, 0.20, P = 0.46) with low heterogeneity (I 2 = 49%) was reported.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations